Increasing Agricultural Production and Farmers Income IFFCOâ€™s initiative at farm level - Roy, A; Kumar, Yogendra; Tiwari, K N (Indian Farming, 2017)
The goal of sustainable high yield agriculture can be successfully achieved with the available resources by motivating the farmers to adopt scientific land, water and integrated nutrient management ensuring maximum input use efficiency. Development of micro-irrigation system will enhance the efficacy of both nutrient and water. The valuable research findings which have waited for long to find place in the Government policy need to be well blended with the package of practices for re-greening the â€œGreen Revolutionâ€. Value addition in Fertilizers and agricultural produce would be essential to make agriculture more efficient and profitable. Reorientation of nutrient and water management options and promotional programs through reenergized marketing and extension services of the Government departments and the fertilizer industry would be essential to tackle multi-facet problems of soil health.